Pengaruh Variasi Umpan Buatan terhadap Hasil Tangkapan Tuna Sirip Kuning dengan Pancing Ulur di Morotai. - Yulianti Istiana; Achmad Kusyairi; Alif Astagia (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Morotai Island Regency is a coastal village so that this area is rich in the potential of marine natural resources, especially fish resources. Generally, fishermen in Morotai Island Regency in utilizing fish resources are still traditional in nature where the average fisherman still uses simple fishing gear, namely a handline using bait as a lure of fish in tuna fishing operations. The benefit to be obtained is to provide information to fishermen about the catch of a handline with the use of different artificial bait as an effective bait, therefore the purpose of this study is 1) Knowing the effect of different types of artificial bait on yellow fin catches ( Thunnus albacares) using a fishing gear (handline) and; 2) Determine the conclusion of artificial bait that is more effective and has the potential to get the catch for use on the fishing gear (handline). This research was located in the waters of Daeo Majiko Village, Morotai Island Regency. The research time was 2 months. This research was conducted using the experimental fishing method with a Randomized Group Design (RAK). The data collected was processed using the ANOVA test, where the aim was to find significant differences between the 3 different types of bait which were the highest baits in obtaining catches during the research.